A Study of Strawberry Leaf Sopts in Al-Jabal El-Akhdar Area, Libya - El-Gali, Zahra I. (Al-Mukhtar Journal of Sciences, 2008)
This study was carried out isolate and determinate the fungus that caused leaf spots on strawberry during 2005- 2006 season. The pathogen was isolated on PDA medium and identified on the basis of classification keys, morphological and cultural characteristies, the results proved that the recoverd isolate from the infected plant tissues belong to Colletotrichum fragariae. Furthermore, the infectivity test of the pathogen supported its determination. The PDA medium was found as the best substrate for fungal growth, and the optimum temperature was 25c° for radial growth and spores germination. The spore germination was started after 8 hr on water Agar surface.